STRATEGI PENGEMBANGAN PANTAI DALAM MENDUKUNG PELESTARIAN LINGKUNGAN PESISIR DI DESA TAWIRI KECAMATAN TELUK AMBON KOTA AMBON - LILIPORY, ISAK LILIPORY, S.T., M.T; Breemer, Jacob (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
This study aims to analyze the development strategy of Tawiri Beach, located in Teluk Ambon District, Ambon City, in supporting coastal environmental conservation using a SWOT analysis approach combined with civil engineering perspectives. Tawiri Village has significant natural potential, strong community support, and a strategic geographic location. The SWOT analysis resulted in a total score of 3.66, positioning the area within the aggressive (Strength–Opportunity) quadrant. This indicates that the development strategy should focus on maximizing internal strengths and external opportunities. The application of civil engineering plays a crucial role in ensuring that tourism development aligns with the principles of environmental sustainability. Key recommendations include the construction of basic infrastructure such as access roads, pedestrian walkways, gazebos, and sanitation facilities using environmentally friendly materials and designs that can withstand coastal climate conditions. In addition, it is essential to implement coastal protection structures such as revetments, natural breakwaters, and shoreline vegetation to mitigate abrasion risks and maintain shoreline stability. Furthermore, the strategy involves designing a coastal spatial plan based on zoning principles, dividing the area into conservation zones, tourism activity zones, and supporting infrastructure zones. Through this approach, beach development not only enhances tourism attractiveness but also promotes comprehensive environmental preservation. The results of this study are expected to serve as a foundation for local government and community stakeholders in planning and implementing sustainable coastal tourism development in Tawiri Village, combining ecological awareness with appropriate civil engineering solutions. Keywords: SWOT, beach development, civil engineering, environmental conservation, Tawiri Village, Ambon.